Expert elicitation, professional judgement, and current exposure assessment practices in the field of occupational hygiene - Lowry, David Michael (Curtin University, 2023)
Occupational hygienists work across a diverse range of industrial environments. In the course of their work, hygienists will need to assess and control worker exposure levels by deploying methods based on the science of risk management, exposure assessment and industrial safety. Hygienists will regularly make decisions relating to worker exposure based on professional judgement, usually in the absence of quantitative data and in the presence of high uncertainty. These factors have the potential to lead to heterogeneity between practitioners, bias, error, and practice variation in the form of departure from established guidelines or protocols. The primary aim of this PhD research project was to examine experience and current practices with respect to exposure assessment processes and judgement amongst occupational hygienists.